Modeling of the processes of nutrient assimilation of soil and cotton plants after exposure to ultraviolet radiation (The Peerian Journal, 2026)
This article presents preliminary theoretical calculations for selecting the power of a bactericidal lamp for ultraviolet irradiation of the "seed-soil-plant" system during cotton cultivation.